Antineoplastic Effect of Procyanidin-rich Extract of Lafoensia Pacari in Lung Carcinoma Cells - Cordeiro,Yonara de Gouveia (2019)
Abstract Lafoensia pacari A. St. Hill has been used in traditional medicine as an anti-ulcerogenic and anti-inflammatory. Although there is an ethnopharmacological indication for cancer treatment, only a few studies have demonstrated its possible anticancer activity. Thus, the aims of this study were: (1) to evaluate the antineoplastic effect of L. pacari ethanolic extract (LPE) in lung carcinoma cells, (2) to determine the mode of action of LPE and (3) to identify the substances present in LPE. Human and murine lung cancer cell lines were grown in vitro and treated with different concentrations of LPE. Cell cycle and caspase-3 activity assays were performed in order to verify the mode of action. LC-ESI-MS screening was performed to detect the compounds present in LPE. LPE showed a dose-dependent cytotoxic effect, where neoplastic cells were more sensitive than non-neoplastic. The LPE induced sub-G1 cell cycle arrest in cancer cells suggesting cell death, which was confirmed as apoptosis by the activation of caspase-3. The LC-ESI-MS analysis indicated a high level of procyanidins, which could be responsible for the antineoplastic effect of LPE. Thus, we concluded that a Lafoensia pacari extract, rich in procyanidins, is cytotoxic against lung cancer cells through activation of caspase-3-dependent apoptosis.